Temperature damage regularity of granite based on micro-inhomogeneity - Du, Guangsheng; Chen, Shijiang; Chen, Xiaoyi; Jiang, Zheng (Frontiers in Earth Science, 2022)
Enhanced geothermal system (EGS) is the primary means during Dry Hot Rock development. It is necessary to build an underground heat exchange area during its construction, and the temperature of underground rock will change significantly, thus, the mechanical properties of those rocks underground will be affected. In order to judge whether the mechanical properties under temperature are related to the crystal structure of granite, we firstly used the crystalline rock heterogeneity coefficient H to describe the crystal structure of granite. Then, the discrete element software was used to construct the GBM equivalent crystalline model and the thermal temperature field coupling model. Finally, the temperature effect test was carried out to explore the law of heterogeneity coefficient H and damage and fracture development. The results show that: 1) the variation of granite heterogeneity coefficient H and temperature will lead to the decline of mechanical properties of rock samples. 2) At the same temperature, the damage value D increases with the increase of the H value. This phenomenon is more apparent when the temperature is greater than 400°C. 3) The microcracks caused by temperature change are mainly tensile. The H value increases the number of microcracks in the crystal. 4) The damage phenomenon caused by temperature change will be affected by heterogeneity. When the temperature is high, the crystal will denature, and the stress concentration caused by heterogeneity is easier to be reflected.